2022
DOI: 10.3390/ijerph20010016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a 4-Week Nurse-Led Exercise Rehabilitation Program in Improving the Quality of Life in Women Receiving a Post-Mastectomy Reconstruction Using the Motiva ErgonomixTM Round SilkSurface

Abstract: We assessed the efficacy of a 4-week nurse-led exercise rehabilitation (ER) program in improving the quality of life (QOL) of breast cancer survivors (BCS) receiving an implant-based breast reconstruction. The eligible patients were equally randomized to either of both groups: the intervention group (n = 30; a 4-week nurse-led ER program) and the control group (n = 30; a 4-week physical therapist-supervised one). Both after a 4-week ER program and at baseline, the patients were evaluated for the European Organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“… Anna et al, [ 42 ] non-blinded randomized controlled trial 577 288 89 58 (12) 58 (11) 15 6 Combined exercise 12 weeks 40–50% of the heart rate reserve HRQOL, assessed using EORTC QLQ- C30 scale Kristiina et al, [ 43 ] Randomized controlled trial 446 106 446 52(7) 53(8) 24.6(3.5) 25.9 (4.1) - - Aerobic exercise 52 weeks - HRQOL, assessed using EORTC QLQ-C30 scale. Jung et al, [ 44 ] prospective, randomized, controlled study 60 28 29 46.9 ( 8.3) 48.1 ( 7.9) 2 1 Combined exercise 4 weeks 40% of maximal oxygen consumption HRQOL, assessed using EORTC QLQ-C30 scale. …”
Section: Resultsmentioning
confidence: 99%
“… Anna et al, [ 42 ] non-blinded randomized controlled trial 577 288 89 58 (12) 58 (11) 15 6 Combined exercise 12 weeks 40–50% of the heart rate reserve HRQOL, assessed using EORTC QLQ- C30 scale Kristiina et al, [ 43 ] Randomized controlled trial 446 106 446 52(7) 53(8) 24.6(3.5) 25.9 (4.1) - - Aerobic exercise 52 weeks - HRQOL, assessed using EORTC QLQ-C30 scale. Jung et al, [ 44 ] prospective, randomized, controlled study 60 28 29 46.9 ( 8.3) 48.1 ( 7.9) 2 1 Combined exercise 4 weeks 40% of maximal oxygen consumption HRQOL, assessed using EORTC QLQ-C30 scale. …”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the Motiva Ergonomix TM Round SilkSurface is the most popular brand of SGBI in Korea. A recent study also reported that breast cancer survivors receiving the Motiva Ergonomix TM Round SilkSurface achieved improvements in quality of life following a 4-week nurse-led exercise rehabilitation [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, long-lasting negative physical and psychological effects are still experienced by BC survivors, including psychosocial distress and physical dysfunction. 5 …”
Section: Introductionmentioning
confidence: 99%
“…However, long-lasting negative physical and psychological effects are still experienced by BC survivors, including psychosocial distress and physical dysfunction. 5 Aerobic training is a beneficial treatment strategy for reducing long-term negative consequences for BC patients. It has several positive effects, including enhanced physical ability, muscular power, and improved psychological wellbeing.…”
Section: Introductionmentioning
confidence: 99%